2018
DOI: 10.1007/s12031-018-1093-3
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of Long Noncoding RNA MALAT1 Protects Hippocampal Neurons Against Excessive Autophagy and Apoptosis via the PI3K/Akt Signaling Pathway in Rats with Epilepsy

Abstract: Epilepsy is a common chronic brain disorder and is characterized by an enduring predisposition to generate seizures. The hippocampus is especially vulnerable to seizure-induced damage. In this study, we explore the ability of long noncoding RNA (lncRNA) metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) to influence the autophagy and apoptosis of hippocampal neurons in epilepsy and the underlying mechanism involving the PI3K/Akt signaling pathway. Seventy-two Sprague-Dawley rats were assigned to n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(60 citation statements)
references
References 38 publications
2
58
0
Order By: Relevance
“…26 MiR-101 is a multiple function molecule, which has been found play a role in maintaining the homeostasis of the neuro system, and abnormal miR-101 level has been identified relates to pathophysiological conditions including spinocerebellar ataxia type 1 and Alzheimer's disease. 18,27,28 miR-101 also functions as an important regulator during the immune response in macrophages. 29 However, roles of miR-101 in the neuroimmune system is still unknown.…”
Section: Resultsmentioning
confidence: 99%
“…26 MiR-101 is a multiple function molecule, which has been found play a role in maintaining the homeostasis of the neuro system, and abnormal miR-101 level has been identified relates to pathophysiological conditions including spinocerebellar ataxia type 1 and Alzheimer's disease. 18,27,28 miR-101 also functions as an important regulator during the immune response in macrophages. 29 However, roles of miR-101 in the neuroimmune system is still unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Image Pro Plus 6.0 (media cybernetics, USA) was used to quantify the gray level of each band, and ÎČactin was used as an internal reference. Each experiment was repeated three times [25].…”
Section: Reverse Transcription Quantitative Polymerase Chain Reactionmentioning
confidence: 99%
“…Following the removal of all blood, the rats stopped autonomous breathing and heartbeat. After the confirmation of rat death, the cranium was opened to extract the brain immediately [7]. The brains were fixed into Bouin's fixative solution for 24 h, dehydrated by gradient alcohol, put into dimethylbenzene, and embedded in paraffin.…”
Section: Hematoxylin-eosin (He) Stainingmentioning
confidence: 99%
“…Findings of Wu et al indicated that lncRNA MALAT1 down-regulation could protect hippocampal neurons against apoptosis and autophagy through promoting the PI3K/Akt signaling pathway in rats with epilepsy [7]. LncRNA nuclear-enriched abundant transcript 1 (NEAT1) is a recently observed crucial factor of nuclear paraspeckles, which has been validated to perform as an oncogene in assorted human cancers, such as pancreatic cancer, colon cancer, glioma and hepatocellular carcinoma [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%